2013
DOI: 10.1155/2013/606258
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Helicobacter pylori Virulence Genes in Gastric Biopsies by PCR

Abstract: Aim. The aim of this study was to identify the presence of H. pylori in biopsy specimens from symptomatic patients by PCR. In addition, the rate of cagA, vacA, iceA1, and iceA2 virulence genes was determined. Materials and Methods. One hundred antral gastric biopsy specimens were collected during endoscopy from patients suffering from gastroduodenal symptoms. The samples were collected by the gastroenterologists in their own clinics in Ramallah, Palestine. DNA was extracted from the biopsies and subsequently u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 22 publications
3
24
0
2
Order By: Relevance
“…The prevalence of H. pylori infection can be attributed to the contribution of specific virulence factors that contribute to the pathogenicity of this organism as enlisted in Table 67.2 Essawi et al, 2013). The prevalence of H. pylori infection can be attributed to the contribution of specific virulence factors that contribute to the pathogenicity of this organism as enlisted in Table 67.2 Essawi et al, 2013).…”
Section: Role Of Virulence Factors In H Pylori Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of H. pylori infection can be attributed to the contribution of specific virulence factors that contribute to the pathogenicity of this organism as enlisted in Table 67.2 Essawi et al, 2013). The prevalence of H. pylori infection can be attributed to the contribution of specific virulence factors that contribute to the pathogenicity of this organism as enlisted in Table 67.2 Essawi et al, 2013).…”
Section: Role Of Virulence Factors In H Pylori Pathogenesismentioning
confidence: 99%
“…pylori genome encodes 32 proteins comprising a cytotoxin CagA and T4SS. Essawi et al (2013) conducted a study to detect the existence of H. pylori along with the rate of cagA, vacA, iceA1, and iceA2 virulence genes in biopsy specimens from symptomatic patients by PCR and found that the rate of positive H. pylori was 44%, while iceA2 was the most frequent virulence gene (84.1%). CagA gene is one of the most important virulence factors located in the DNA segment termed as cag pathogenicity island (cagPAI).…”
Section: Role Of Cagamentioning
confidence: 99%
“…Molecular methods are widely used to diagnose H. pylori infections as well as for analyses of virulence diversity and resistance patterns of these bacterial strains [4,5]. However, the high degree of genomic plasticity among strains of H. pylori caused the complexity of choosing the target genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high degree of genomic plasticity among strains of H. pylori caused the complexity of choosing the target genes. Even nucleotide sequences that are highly conserved in various strains of the pathogen, such as urease A (ureA), urease C (glmM) and 16S rRNA, may fail to detect the bacteria [4,6]. Therefore, another virulence genes can be detected as vacA, cagA genes to confirm the presence of virulent H. pylori strains [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…33 The first gene of pathogenicity identified in H. pylori was cagA. This gene is highly prevalent in strains from different geographic areas.…”
mentioning
confidence: 99%